Praktek Penggunaan Teknologi Pendidikan Pada Pendidikan Informal Anak Usia Dini - Pinilih, Yogi (Indonesian Journal of Learning and Instructional Innovation, 2023)
The development of the world of science and technology is increasingly unimaginable by theabilities of ordinary human minds, therefore knowledge, skills and attitudes are needed that cankeep up with the current developments and advances in science and technology as a way tokeep pace with the development and progress of science and technology. the. The existence oftechnology cannot be denied and however children cannot be prevented or prohibited fromusing it, proper control and assistance can be the right solution for children. Becausetechnology is inseparable from life in this increasingly sophisticated era. Furthermore, thepractice of educators is required to master science and technology in transferring subject matterto students, so that students learn in the learning process will be more appropriate andmeaningful. Early childhood informal educational institutions as producers of human resourceswith all the elements of its implementation are one of the keys in facing the era of technologyand information. Informal education paths are given to every individual from birth andthroughout his life, both through his family and environment. This educational path willbecome the foundation that will shape one's habits, character and behavior in the future.